2013
DOI: 10.1371/journal.pone.0063459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Susceptibility Weighted Imaging and TOF-Angiography for the Detection of Thrombi in Acute Stroke

Abstract: Background and PurposeTime-of-flight (TOF) angiography detects embolic occlusion of arteries in patients with acute ischemic stroke due to the absence of blood flow in the occluded vessel. In contrast, susceptibility weighted imaging (SWI) directly enables intravascular clot visualization due to hypointense susceptibility vessel signs (SVS) in the occluded vessel. The aim of this study was to compare the diagnostic accuracy of both methods to determine vessel occlusion in patients with acute stroke.Methods94 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
5
41
1
Order By: Relevance
“…Among 34 patients with MCA occlusion, SVS was demonstrated in 30 on SWI. Our results were similar to those of recent studies, in which SWI showed high sensitivity (75-93%) and specificity (90%) for the detection of the major intracranial arterial occlusion in acute stroke patients (19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…Among 34 patients with MCA occlusion, SVS was demonstrated in 30 on SWI. Our results were similar to those of recent studies, in which SWI showed high sensitivity (75-93%) and specificity (90%) for the detection of the major intracranial arterial occlusion in acute stroke patients (19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…Mean age was 69±15 years, median National Institutes of Health Stroke Scale was 16 (interquartile range, [12][13][14][15][16][17][18][19][20], and proximal occlusion (internal carotid artery or M1) was present in 83% of patients. Unexplained END occurred in 22 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SVS extension or regression might reflect structural or metabolic changes within the thrombus over time rather than true thrombus evolution, 15,16 which may explain why 10 patients had complete regression of SVS on follow-up MRI, despite persistent occlusion on MRA. Although some MR sequences, such as susceptibility-weighted imaging, are more sensitive than T2* for thrombus detection, 10,17,18 they are more timeconsuming and particularly their use in the hyperacute stroke setting is questionable. Lastly, the purposely devised assessment of SVS extension relied on qualitative, although expertbased, visual image analysis.…”
Section: February 2017mentioning
confidence: 99%
“…It has been used for the detection of cerebral microbleeds or intracranial hemorrhage for many years [8]. Recently, changes in cortical and deep medullary vessels were described in [9][10][11][12][13][14][15][16]. Signs for hypoperfusion have been described in T2*-weighted imaging before, but due to the calculation of the SWI maps explained above, the findings are more prominent and therefore easier to examine on SWI [17].…”
Section: Introductionmentioning
confidence: 99%